Asymmetric hollow fiber membrane and production method of the same

JP2025028703APending Publication Date: 2025-03-03MITSUI CHEMICALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023133675
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-03-03

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、非常に高い気体流速および高いCO2/N2選択性を有し、かつ、均一な孔径および高い多孔度を有する非対称中空糸膜を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025028703000007
    Figure 2025028703000007
  • Figure 2025028703000008
    Figure 2025028703000008
  • Figure 2025028703000009
    Figure 2025028703000009
Patent Text Reader

Abstract

To provide an asymmetric hollow fiber membrane having an extremely high gas flow rate, high CO2 / N2 selectivity, a uniform bore diameter and high porosity.SOLUTION: An asymmetric hollow fiber membrane comprises: a porous base material including a semi-crystalline thermoplastic polymer (A) where a plurality of pores is possessed, a content of a constitutional unit (i) derived from 4-methyl-1-pentene is more than 99.4 mol% and 100 mol% or less and a content of a constitutional unit (ii) derived from at least one kind selected from α-olefins having a carbon atom number of 2-20 is 0 mol% or more and less than 0.6 mol%; and including a skin layer including a semi-crystalline thermoplastic copolymer (B) where the content of the constitutional unit (iii) derived from 4-methyl-1-pentene is 0.5 mass% or more and 98 mass% or less and the content of a constitutional unit (iv) derived from at least one kind selected from α-olefins having a number of carbon atom 2-20 is 2 mass% or more and 99.5 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an asymmetric hollow fiber membrane and a method for producing the same. [Background technology]

[0002] Microporous hollow fibers can be used to separate components from a fluid stream based on size, phase, charge, etc. Microporous hollow fibers often employ materials with controlled porosity and pore size, often on the order of a few microns, and can have many uses, including, for example, separation, filtration, diffusion, and barrier applications (Patent Document 1). These broad applications have practical applications in medical devices, electrochemical devices, chemical processing devices, pharmaceutical equipment, and water purification, to name a few.

[0003] The functionality of microporous hollow fiber membranes is often a complex function of the specific end use, the structure of the hollow fiber (e.g., hollow fiber diameter, wall thickness, porosity, pore size, and pore tortuosity), and the composition or chemistry of the asymmetric hollow fiber membrane surface. Often, these and other variables of the hollow fiber must be tailored to the specific end use. For example, membranes with gas-permeable separation layers can be used to provide selective gas / gas and / or gas / liquid passages.

[0004] Asymmetric microporous hollow fiber membranes allow the selective passage of dissolved gases and the blocking of liquid water or other aqueous liquids, and may be advantageously used in membrane contactors to achieve gas / liquid separations in certain applications, such as the degassing of aqueous printing inks during printing, or the separation of dissolved gases such as carbon dioxide or methane from aqueous brines used to enhance oil recovery (Patent Document 2).

[0005] At least certain known microporous hollow fiber membranes have been found to be less than entirely satisfactory in some particular gas / liquid separation applications under certain operating conditions. Thus, a need exists for improved hollow fiber membrane contactors that have improved design or operating characteristics over known membrane contactors designed for particular end uses.

[0006] For example, given environmental concerns, the desire to separate components, the need to protect equipment, and / or efforts to improve process efficiency, it is often necessary or desirable to remove one or more components or contaminants from an effluent stream, e.g., so that the components or contaminants do not pollute the environment, adversely affect equipment, or so that they can be recycled. Existing industrial processes must frequently be upgraded to reduce environmental emissions and / or to increase efficiency. Thus, there is often a need for processes and systems that can be economically retrofitted to existing plants to reduce emissions, protect equipment, recycle, or improve efficiency.

[0007] Thus, there is also a need for improved microporous hollow fiber membrane materials that can be used in a wider range of applications and that can perform better for specific purposes, under specific operating conditions, etc. There is also a need for improved membrane contactors having improved designs or properties over known membrane contactors for use in gas / liquid separations in specific applications, such as degassing aqueous printing inks during printing, or separating dissolved gases such as carbon dioxide or methane from aqueous brines used to enhance oil recovery. It is an object of at least certain exemplary embodiments of the present disclosure to provide asymmetric microporous hollow fiber membrane devices that meet these and other needs. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] WO2018 / 128688 publication [Patent Document 2] WO2012 / 138755 publication Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide an asymmetric hollow fiber membrane having very high gas flow rate and high CO2 / N2 selectivity, as well as uniform pore size and high porosity. [Means for solving the problem]

[0010] As a result of intensive research aimed at solving the above problems, the present inventors have found that the above problems can be solved by the following embodiments, and have completed the present invention.

[0011] [1] A porous substrate comprising a semi-crystalline thermoplastic polymer (A) having a plurality of pores, the content of structural units (i) derived from 4-methyl-1-pentene being more than 99.4 mol% and not more than 100 mol%, and the content of structural units (ii) derived from at least one selected from α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) being 0 mol% or more and less than 0.6 mol% (the sum of the content of the structural units (i) and the content of the structural units (ii) is 100 mol%); a skin layer comprising a semi-crystalline thermoplastic copolymer (B) having a content of 0.5% by mass or more and 98% by mass or less of structural units (iii) derived from 4-methyl-1-pentene and a content of 2% by mass or more and 99.5% by mass or less of structural units (iv) derived from at least one selected from α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) (the total of the content of the structural units (iii) and the content of the structural units (iv) is taken as 100% by mass); An asymmetric hollow fiber membrane comprising: [2] The asymmetric hollow fiber membrane according to item [1], wherein the plurality of pores includes a plurality of micropores, and the plurality of micropores has a diameter of 0.01 to 1.0 μm. [3] The asymmetric hollow fiber membrane according to item [1] or [2], wherein the porosity of the asymmetric hollow fiber membrane is 5 to 80%. [4] The asymmetric hollow fiber membrane according to any one of items [1] to [3], wherein the skin layer has a lower porosity than the porous substrate, an outer surface of the asymmetric hollow fiber membrane forms a sheath, and the porous substrate forms an inner lumen surface of the asymmetric hollow fiber membrane. [5] The asymmetric hollow fiber membrane according to item [4], wherein the skin layer is non-porous. [6] The asymmetric hollow fiber membrane according to any one of items [1] to [5], wherein the porous substrate further contains 200 ppm to 5 mass % of a nucleating agent (where the porous substrate is taken as 100 mass %). [7] The asymmetric hollow fiber membrane according to any one of items [1] to [6], wherein the thickness of the skin layer is 1.0 μm or more and less than 20 μm. [8] The asymmetric hollow fiber membrane according to any one of items [1] to [7], wherein the porous substrate has a thickness of 5 to 200 μm. [9] The asymmetric hollow fiber membrane according to any one of items [1] to [8], wherein the asymmetric hollow fiber membrane is a heterogeneous asymmetric hollow fiber membrane.

[10] The asymmetric hollow fiber membrane according to any one of items [1] to [9], wherein the skin layer completely covers the porous substrate.

[11] A separation article comprising a plurality of the asymmetric hollow fiber membranes according to any one of items [1] to

[10] .

[12] The separation article according to item

[11] , wherein the plurality of asymmetric hollow fiber membranes are arranged in an array, and the array is pleated, folded, or rolled to form a cylinder or cassette.

[13] The separation article according to item

[11] or

[12] , which is selectively permeable to CO2 over N2 or CH4.

[14] The separation article according to item

[13] , having a CO2 / N2 or CO2 / CH4 selectivity of 8 or more.

[15] The separation article according to any one of items

[11] to

[14] , which has selective permeability to O2 over N2.

[16] A method for producing an asymmetric hollow fiber membrane comprising a porous substrate and a skin layer, comprising: The base resin constituting the porous base material contains a semi-crystalline thermoplastic polymer (A) having a content of 4-methyl-1-pentene-derived structural unit (i) of more than 99.4 mol % and not more than 100 mol % and a content of at least one structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) of 0 mol % or more and less than 0.6 mol % (the sum of the content of the structural unit (i) and the content of the structural unit (ii) is 100 mol %); the skin layer resin constituting the skin layer contains a semi-crystalline thermoplastic copolymer (B) having a content of 4-methyl-1-pentene-derived structural unit (iii) of 0.5% by mass or more and 98% by mass or less and a content of at least one structural unit (iv) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) of 2% by mass or more and 99.5% by mass or less (the sum of the content of the structural unit (iii) and the content of the structural unit (iv) is taken as 100% by mass); (1) co-extruding the substrate resin and the skin layer resin to form an asymmetric hollow fiber membrane precursor; (2) stretching the asymmetric hollow fiber membrane precursor to form an asymmetric hollow fiber membrane having a skin layer composed of the skin layer resin on a porous substrate composed of the base resin and including a plurality of pores; A method for producing an asymmetric hollow fiber membrane comprising the steps of:

[17] The method for producing an asymmetric hollow fiber membrane according to item

[16] , wherein the skin layer resin does not contain a pore-forming material.

[18] The method for producing an asymmetric hollow fiber membrane according to item

[17] , wherein the step (1) includes a step (3) of co-extruding the base resin and the skin layer resin through an annular co-extrusion die to form the asymmetric hollow fiber precursor.

[19] The method for producing an asymmetric hollow fiber membrane according to any one of items

[16] to

[18] , further comprising a step (4) of annealing the asymmetric hollow fiber precursor.

[20] The method for producing an asymmetric hollow fiber membrane according to item

[19] , wherein the step (4) is performed before stretching the asymmetric hollow fiber precursor. Effect of the Invention

[0012] According to the present invention, it is possible to provide an asymmetric hollow fiber membrane having a very high gas flow rate and high CO2 / N2 selectivity, as well as a uniform pore size and high porosity. [Brief description of the drawings]

[0013] The present disclosure may be more fully understood from the following detailed description of various embodiments of the disclosure when considered in conjunction with the accompanying drawings, in which: [Figure 1] FIG. 2 is a close-up surface view of an exemplary hollow fiber membrane array useful in producing a porous membrane contactor according to certain embodiments of the present disclosure. [Diagram 2] FIG. 2 is an enlarged perspective view of an end of an exemplary hollow fiber membrane according to certain embodiments of the present disclosure. [Diagram 3] FIG. 4 is an enlarged surface view of a portion of the porous substrate layer forming the interior of the hollow fiber of FIG. 3, in accordance with certain embodiments of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] With regard to the following glossary of defined terms, these definitions shall apply throughout this application, unless a different definition is provided in the claims or elsewhere in this specification.

[0015] [Terminology] Certain terms are used throughout this specification and claims, most of which are well known, but may require some explanation. Thus, the following should be understood:

[0016] The term "(co)polymer" or "singular" includes homopolymers and copolymers, as well as homopolymers or copolymers that may be formed in miscible blends, for example, by coextrusion or by reaction, including, for example, transesterification. The term "copolymer" includes random copolymers, block copolymers, and star (e.g., dendritic) copolymers.

[0017] The term "semi-crystalline" with respect to a (co)polymer is intended to refer to both partially crystalline and fully crystalline (co)polymers, where the (co)polymer exhibits a crystalline melting temperature as determined using differential scanning calorimetry.

[0018] The term "hollow fiber membrane" means an artificial semipermeable barrier in the form of open tubular filaments of indefinite length.

[0019] The term "asymmetric" with respect to hollow fiber membranes means that the membrane has two major surfaces, a lumen surface, and an outer sheath surface, that are composite and / or structurally and / or functionally distinct.

[0020] The term "homogeneous" means exhibiting only a single phase of material when observed on a macroscopic scale.

[0021] The term "microporous" with respect to hollow fiber membranes means that the membrane is formed from a solid matrix having defined, generally circular openings or holes (pores) formed therein, where the pores generally have a diameter of at least 10 nm and less than 1 mm.

[0022] The term "non-porous" refers to a dense film in which the permeant is transported by diffusion under the driving forces of concentration, pressure, or potential gradients.

[0023] The term "nucleating agent" means a material that promotes crystallization (nucleation) of semicrystalline polymers during melt processing.

[0024] The term "adjacent" with respect to a particular layer means that the two layers are adjacent (i.e., adjacent) and in direct contact with one another, or are joined or attached to another layer in a position that is adjacent but not in direct contact with one another (i.e., with one or more additional layers intervening between the layers).

[0025] For the location of various elements in the disclosed coated articles, orientation terms such as "atop," "on," "over," "covering," "uppermost," "overlaying," "underlying," etc. are used to refer to the relative position of the elements with respect to a horizontally positioned, upward-facing substrate. However, unless otherwise indicated, it is not intended that the substrate or article should have any particular spatial orientation during or after manufacture.

[0026] Use of the term "overcoated" to describe the location of a layer relative to a substrate or other element of an article of the present disclosure refers to the layer being on top of, but not necessarily in close proximity to, the substrate or other element.

[0027] By using the term "separated by" to describe the location of a layer relative to other layers, we are referring to the layer being located between two other layers, but not necessarily adjacent or contiguous to either layer.

[0028] The terms "about" or "approximately" with reference to a numerical value or shape mean ±5 percent of the numerical value or property or characteristic, but expressly include the exact numerical value. For example, a viscosity of "about" 1 Pa·sec refers to a viscosity between 0.95 and 1.05 Pa·sec, but also expressly includes a viscosity of exactly 1 Pa·sec. Similarly, a "substantially square" perimeter is intended to describe a geometric shape having four lateral edges, each lateral edge having a length that is between 95 and 105% of the length of any other lateral edge, but is also intended to include geometric shapes in which each lateral edge has the exact same length.

[0029] The term "substantially" with respect to a property or characteristic means that the property or characteristic is exhibited to a greater extent than the opposite of the property or characteristic is exhibited. For example, a "substantially" transparent substrate refers to a substrate that transmits more radiation (e.g., visible light) than it does not transmit (e.g., absorbs and reflects). Thus, a substrate that transmits more than 50% of the visible light incident on its surface is substantially transparent, while a substrate that transmits 50% or less of the visible light incident on its surface is not substantially transparent.

[0030] As used herein and in the accompanying embodiments, the singular includes plural referents unless the context clearly dictates otherwise. Thus, for example, reference to a microfiber containing a "compound" includes a mixture of two or more compounds. As used herein and in the accompanying embodiments, the term "or" is generally utilized in the sense of including "and / or" unless the context clearly dictates otherwise.

[0031] As used herein, the recitations of numerical ranges by endpoints include all numbers subsumed within that range (eg, 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.8, 4, and 5).

[0032] Unless otherwise indicated, all numbers expressing quantities or components, property measurements, and the like used in the specification and embodiments are to be understood in all instances as being modified by the term "about". Accordingly, unless otherwise indicated, the numerical parameters set forth in the foregoing specification and the accompanying enumeration of embodiments may vary depending on the desired properties one of ordinary skill in the art would obtain using the teachings of the present disclosure. At the very least, each numerical parameter should at least be construed in light of the number of reported significant digits and by applying ordinary rounding techniques, which is not intended to limit the application of the doctrine of equivalents to the scope of the claimed embodiments. Additionally, the various monomers in the present disclosure may be derived from fossil raw materials or biomass.

[0033] Various exemplary embodiments of the present disclosure will be described below with specific reference to the drawings. Various modifications and changes may be made to the exemplary embodiments of the present disclosure without departing from the spirit and scope of the present disclosure. Therefore, it should be understood that the embodiments of the present disclosure are not limited to the exemplary embodiments described below, but are governed by the limitations set forth in the claims and any equivalents thereof.

[0034] <Asymmetric hollow fiber material> Referring now to FIG. 2, in one embodiment, the present disclosure describes an asymmetric hollow fiber membrane 202 that includes a porous substrate 204 having a plurality of pores and a skin layer 206 overlying the porous substrate 204.

[0035] As shown in FIG. 3, the surface 310 of the porous substrate has a plurality of pores 308. In preferred embodiments, the plurality of pores comprises micropores. In some such embodiments, the micropores have a diameter of preferably 0.01-1.0 μm, more preferably 0.02-0.5 μm, and even more preferably 0.03-0.3 μm. In further exemplary embodiments, the asymmetric hollow fiber membrane is preferably 5-80%, more preferably 10-50%, and even more preferably 15-40%.

[0036] In a preferred embodiment, the skin layer completely covers the porous substrate. In some exemplary embodiments, the skin layer is less porous than the porous substrate and constitutes the outer surface of the asymmetric hollow fiber membrane. In some such embodiments, the porous substrate constitutes the lumen surface, and the skin layer constitutes the sheath of the outer surface of the asymmetric hollow fiber membrane. Examples of materials that constitute the sheath include 4-methyl-1-pentene-based polymers. In a preferred embodiment, the skin layer is non-porous.

[0037] In some exemplary embodiments, the skin layer has a thickness of preferably 1.0 μm or more and less than 20 μm, more preferably 1.5 μm or more and less than 5 μm, and even more preferably 2.0 μm or more and less than 4.5 μm. In certain such exemplary embodiments, the porous substrate has a thickness of preferably 5 to 200 μm, more preferably 10 to 100 μm, even more preferably 20 to 50 μm, and especially preferably 5 to 10 μm.

[0038] In further exemplary embodiments, the asymmetric hollow fiber membrane is a heterogeneous asymmetric hollow fiber membrane. In certain such embodiments, the skin layer is non-porous or exhibits small diameter pores and the porous substrate exhibits larger diameter pores. In some such embodiments, the membrane morphology is radially isotropic.

[0039] In certain exemplary embodiments, the asymmetric microporous hollow fiber membrane exhibits the following properties: CO2 gas permeation rate of 22-36 GPU (1 GPU=10 6 scc / cm 2 ·sec·cmHg, CO2 / N2 selectivity of 13–14 (e.g., 13.85), skin layer thickness of 1.5–2.5 μm, total asymmetric microporous hollow fiber porosity of approximately 40%, fiber outer diameter (OD) of approximately 300 μm, fiber wall thickness of 20–40 μm, and total coverage of the skin layer on the porous substrate (i.e., 100%).

[0040] [Materials for producing asymmetric hollow fiber components] Asymmetric hollow fiber membranes can be constructed using a variety of materials, including, but not limited to, thermoplastic (co)polymers such as polyolefin copolymers. In a currently preferred implementation, the microporous asymmetric hollow fiber includes a skin layer 206 comprised of a semi-crystalline thermoplastic polymer (A) disposed on a porous substrate 204 comprised of a semi-crystalline thermoplastic copolymer (B).

[0041] In some exemplary embodiments, the semicrystalline thermoplastic polymer (A) exhibits a melting temperature (Tm) higher than the melting temperature of the semicrystalline thermoplastic copolymer (B). In other exemplary embodiments, the semicrystalline thermoplastic polymer (A) has a higher crystallinity than the semicrystalline thermoplastic copolymer (B). In certain such exemplary embodiments, the crystallinity of the semicrystalline thermoplastic polymer (A) is at least 40% by weight. In some such exemplary embodiments, the crystallinity of the semicrystalline thermoplastic copolymer (B) is less than about 40% by weight. In further exemplary embodiments, the semicrystalline thermoplastic polymer (A) has a higher modulus than the semicrystalline thermoplastic copolymer (B).

[0042] [Porous base resin] The porous substrate 204 is composed of a semi-crystalline thermoplastic polymer (A) having a content of structural units (i) derived from 4-methyl-1-pentene of more than 99.4 mol % and not more than 100 mol %, and a content of structural units (ii) derived from at least one selected from α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) of 0 mol % or more and less than 0.6 mol %, where the sum of the content of the structural units (i) and the content of the structural units (ii) is 100 mol %.

[0043] The porous substrate resin satisfies the following requirement (a).

[0044] 《Requirement (a)》 The (a) porous substrate resin has a content of structural unit (i) of more than 99.4 mol% and not more than 100 mol%, and a content of structural unit (ii) of 0 mol% or more and less than 0.6 mol%, preferably a content of structural unit (i) of 99.5 to 100 mol%, and a content of structural unit (ii) of 0 to 0.5 mol%, more preferably a content of structural unit (i) of more than 99.5 mol% and not more than 100 mol%, and a content of structural unit (ii) of 0 mol% or more and less than 0.5 mol%, even more preferably a content of structural unit (i) of 99.6 to 100 mol%, and a content of structural unit (ii) of 0 to 0.4 mol%, and particularly preferably a content of structural unit (i) of more than 99.6 mol% and not more than 100 mol%, and a content of structural unit (ii) of 0 mol% or more and less than 0.4 mol%.

[0045] It is preferable that the porous base resin satisfies the above-mentioned content of the structural unit from the viewpoint of heat resistance and light weight.In addition, it is preferable that the content of the structural unit (ii) is small and the crystallinity is high, and the separation article of the asymmetric hollow fiber membrane containing the porous base resin has excellent gas permeability and CO2 / N2 selectivity.

[0046] Examples of α-olefins having 2 to 20 carbon atoms include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. Among these, from the viewpoint of imparting flexibility to the asymmetric hollow fiber membrane obtained from the porous substrate resin, linear α-olefins having 5 to 20 carbon atoms are preferred, linear α-olefins having 6 to 20 carbon atoms are more preferred, linear α-olefins having 8 to 20 carbon atoms are even more preferred, and linear α-olefins having 10 to 20 carbon atoms are particularly preferred. Specifically, 1-hexene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, and 1-octadecene are preferred, and 1-decene, 1-tetradecene, 1-hexadecene, and 1-octadecene are particularly preferred. When the porous substrate resin has the structural unit (ii), the structural unit (ii) may be one type alone or two or more types.

[0047] The porous base resin may further have a structural unit derived from a polymerizable compound other than 4-methyl-1-pentene and α-olefins having 2 to 20 carbon atoms, within a range that does not impair the object of the present invention. Examples of the other polymerizable compounds include vinyl compounds having a cyclic structure, such as styrene, vinylcyclopentene, vinylcyclohexane, and vinylnorbornane; vinyl esters, such as vinyl acetate; unsaturated organic acids or derivatives thereof, such as maleic anhydride; conjugated dienes, such as butadiene, isoprene, pentadiene, and 2,3-dimethylbutadiene; 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, Examples of non-conjugated polyenes include dicyclopentadiene, cyclohexadiene, dicyclooctadiene, methylenenorbornene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, and 2-propenyl-2,2-norbornadiene. In the porous substrate resin, the content of the structural unit derived from other polymerizable compounds is usually 0.5 mol% or less, preferably 0.3 mol% or less, more preferably 0.1 mol% or less, based on 100 mol% of all structural units, and it is particularly preferable that it is not contained.

[0048] In addition to the above requirement (a), the porous substrate resin preferably further satisfies one or more of the following requirements (b) to (h).

[0049] 《Requirement (b)》 (b) 13The meso dyad fraction (m) measured by C-NMR is preferably 98.5% or more and 100% or less. The meso dyad fraction (m) of the porous substrate resin is more preferably 98.7 to 100%, even more preferably 99.0 to 100%, particularly preferably 99.3 to 100%, and extremely preferably 99.5 to 100%. When the meso dyad fraction (m) of the porous substrate resin satisfies the above range, the heat resistance and mechanical strength of the obtained asymmetric hollow fiber membrane are sufficient. In the present invention, the meso dyad fraction (m) of the porous substrate resin can be adjusted by the type of olefin polymerization catalyst described in, for example, JP 2022-171595 A.

[0050] 《Requirement (c)》 (c) The intrinsic viscosity [η] measured in decalin solvent at 135°C is preferably 0.1 to 6.0 dl / g. The intrinsic viscosity [η] of the porous substrate resin is more preferably 1.2 to 3.6 dl / g, further preferably 1.4 to 3.4 dl / g, and particularly preferably 1.6 to 3.2 dl / g. If the intrinsic viscosity [η] is too large, the surface roughness and thickness unevenness of the separation article of the asymmetric hollow fiber membrane obtained tend to increase due to disturbance of the resin flow inside the die during molding and phenomena due to melt fracture. In addition, if the intrinsic viscosity [η] is too small, it is considered that the thickness unevenness tends to increase due to edge vibration and lifting from the chill roll caused by a decrease in melt tension. If the intrinsic viscosity [η] of the porous substrate resin satisfies the above range, it is preferable because it is easy to obtain a separation article with excellent moldability and no thickness unevenness.

[0051] 《Requirement (d)》 (d) The amount of 23°C decane solubles is preferably 5.0% by mass or less. The amount of 23°C decane solubles of the porous substrate resin is more preferably 3.0% by mass or less, even more preferably 1.0% by mass or less, particularly preferably 0.5% by mass or less, and extremely preferably 0.1% by mass or less. When the amount of 23°C decane solubles of the porous substrate resin satisfies the above range, the crystallinity of the porous substrate resin becomes high, and a separation article containing the same is preferable because it has excellent gas permeability and CO2 / N2 selectivity.

[0052] 《Requirement (e)》 (e) The melting point (Tm) measured by differential scanning calorimetry (DSC) is preferably 200 to 260° C. The melting point (Tm) of the porous substrate resin is more preferably 210 to 255° C., further preferably 220 to 250° C., and particularly preferably 230 to 245° C. If the porous substrate resin satisfies the above range, the separation article containing it will have excellent heat resistance, which is preferable.

[0053] 《Requirement (f)》 (f) The heat of fusion (ΔHm) measured by differential scanning calorimetry (DSC) is preferably 45 J / g or more. The heat of fusion (ΔHm) of the porous substrate resin is more preferably 48 J / g or more, even more preferably 50 J / g or more, and particularly preferably 52 J / g or more. The upper limit of this heat of fusion (ΔHm) is not particularly limited, but is, for example, 70 J / g. The porous substrate resin satisfies the above range and has a high degree of crystallinity, and a separation article containing it is preferable because it has excellent heat resistance, gas permeability, and CO2 / N2 selectivity.

[0054] The porous substrate resin preferably has the above-mentioned melting point (Tm) and heat of fusion (ΔHm) satisfying the following formula (1), more preferably the following formula (2), even more preferably the following formula (3), and particularly preferably the following formula (4). ΔHm-(0.5×Tm-76)≧0 … (1) ΔHm-(0.5×Tm-76)>0 …(2) ΔHm-(0.5×Tm-76)≧6 … (3) ΔHm-(0.5×Tm-76)≧8 … (4)

[0055] The upper limit of ΔHm-(0.5×Tm-76) is not particularly limited, but is, for example, 20. When it is in this range, it is preferable because it is possible to obtain excellent heat resistance, suppress gas permeation, and is easy to obtain a separation article that is excellent in moldability and has a uniform thickness. The porous substrate resin satisfying the above formula has a larger heat of fusion (ΔHm) at the same melting point (Tm) than the conventionally known 4-methyl-1-pentene polymers, that is, has a higher degree of crystallinity.

[0056] 《Requirement (g)》 (g) The density measured in accordance with the density gradient tube method of JIS K7112 is preferably 815 to 850 kg / m 3 The density of the porous substrate resin is more preferably 820 to 840 kg / m 3 and more preferably 825 to 835 kg / m 3 and particularly preferably 825 to 832 kg / m 3 It is. When the density of the porous base resin satisfies the above range, the separation article containing the same is preferably lightweight. The 4-methyl-1-pentene polymer (X) of the present invention that satisfies the above range has excellent heat resistance, gas permeability, and CO2 / N2 selectivity, even though the molded article containing the same is lightweight.

[0057] 《Requirements (h)》 (h) The melt flow rate (MFR) measured according to ASTM D1238 at 260°C under a load of 5 kg is preferably 0.1 to 500 g / 10 min. The melt flow rate (MFR) of the porous substrate resin is more preferably 2 to 100 g / 10 min, and further preferably 3 to 30 g / 10 min. A melt flow rate (MFR) within the above range is preferable in terms of the resin fluidity during the production of a molded article (separated article). In the present invention, the melt flow rate (MFR) of the porous substrate resin can be adjusted, for example, by making hydrogen coexist in a reactor during the polymerization reaction.

[0058] [Skin layer resin] The skin layer resin 206 is composed of a semi-crystalline thermoplastic copolymer (B) having a content of structural units (iii) derived from 4-methyl-1-pentene of 0.5% by mass or more and 98% by mass or less, and a content of structural units (iv) derived from at least one selected from α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) of 2% by mass or more and 99.5% by mass or less (the sum of the content of the structural units (iii) and the content of the structural units (iv) is 100% by mass).

[0059] The α-olefin having 2 to 20 carbon atoms, excluding 4-methyl-1-pentene, may be selected from the group consisting of ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, isobutylene, vinylcyclohexane, 3-ethyl-1-pentene, 1,3-methyl-1-pentene, cyclobutene, cyclopentane, 2-norbornene, 3-methyl-2-norbornene, 5-methyl-2-norbornene, tetracyclododecene, methyltetracyclododecene, dimethyltetracyclododecene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-eicosene, or a combination thereof.

[0060] The amount of 4-methyl-1-pentene monomer used in the semicrystalline thermoplastic polymer (A) differs from the amount of 4-methyl-1-pentene monomer used in the semicrystalline thermoplastic copolymer (B) by at least preferably 0.5% by weight, more preferably 0.75% by weight, even more preferably 1% by weight, and particularly preferably 1.5% by weight.

[0061] In some embodiments, the substrate resin may advantageously comprise one or more (methyl)pentene (PMP) resins having a crystallinity different from that of the PMP skin layer resin, polyethylene (PE), polypropylene (PP), or combinations thereof.

[0062] In various implementations involving multi-layer microporous membranes, the PMP skin may be disposed as any layer of a multi-layer asymmetric hollow fiber, for example, the PMP skin may constitute one or more outer and / or inner layers of a multi-layer asymmetric hollow fiber that includes multiple layers, for example, three or more layers. Furthermore, in the case of hollow fiber asymmetric hollow fibers, the PMP skin may be disposed on the shell side or the lumen side of such hollow fiber asymmetric hollow fiber.

[0063] Asymmetric hollow fibers may have a PMP skin layer that differs from the substrate according to one or more physical properties. For example, each of the skin and substrate may be formed from a PMP resin, but the crystallinity of each of the skin and substrate may differ, resulting in a non-uniform asymmetric hollow fiber. In an exemplary implementation, the PMP resin for the skin has a crystallinity of about 40% or less than 40%, while the PMP resin for the substrate has a crystallinity of about 40% or more, for example, a crystallinity of about 60% or more. The crystallinity of the PMP affects the porosity of the material, and a higher crystallinity can result in a more porous asymmetric hollow fiber compared to a lower crystallinity. Correspondingly, the porosity of the material can affect the permeability of the asymmetric hollow fiber to solid, liquid, and gaseous materials.

[0064] In some exemplary implementations, the physical properties of the PMP skin and substrate may differ based on the copolymer composition used to form the skin and substrate. For example, if the skin is formed from a PMP having more α-olefin comonomer, the substrate may form less α-olefin comonomer. The gas permeability of the PMP skin may be a benefit or advantage of the membranes described herein. By way of example only, in some implementations, the PMP skin may efficiently vaporize and / or degas a liquid without being permeable to the liquid.

[0065] Additionally, the temperature stability of the membranes described herein may be improved over other known membranes because the melting point of the PMP skin resin may add temperature stability to the asymmetric hollow fibers.

[0066] Additionally, asymmetric hollow fibers formed from a PMP skin layer and a PE or PP microporous substrate layer can offer the benefit of having higher gas permeability than other membranes due to the high porosity of the microporous substrate. In various implementations described herein, microporous substrates having porosities of greater than 20%, greater than 25%, greater than 35%, or greater than 40% can be used.

[0067] The PMP skin may be a non-porous skin, such as a solid skin without pores (or a skin that is impermeable to liquids but permeable to gases) disposed on a microporous substrate. The PMP skin is substantially free of defects. The precision of the PMP skin may result from the dry stretching process (or CELGARD® process) by which the microporous membranes of the present invention are produced, as further described herein.

[0068] The thickness of the PMP skin and substrate may depend on the particular application in which the microporous asymmetric hollow fiber is employed. In exemplary implementations, the PMP skin may be 20 μm or less in thickness, or 5 μm or less in thickness, or 3 μm or less in thickness, or about 2 μm in thickness. In various implementations, reducing the thickness of the PMP skin results in a more efficient asymmetric microporous asymmetric hollow fiber.

[0069] In various implementations, the substrate may have a thickness ranging from 5 to 200 μm, 10 to 100 μm, 15 to 75 μm, 20 to 50 μm, or 25 to 35 μm. In some implementations, the substrate may have an even smaller thickness (e.g., less than 5 μm) in various film and / or flat sheet implementations.

[0070] Based on nuclear magnetic resonance (NMR) analysis, α-olefin comonomers having 2 to 20 carbon atoms, excluding 4-methyl-1-pentene, have been identified in poly(methyl)pentene copolymers. The inventors have found that the use of poly(methyl)pentene with an amount of α-olefin having 2 to 20 carbon atoms, excluding 4-methyl-1-pentene, as a comonomer less than 2.3% by weight can only lead to a defective skin layer. On the other hand, poly(methyl)pentene with sufficient α-olefin comonomer having 2 to 20 carbon atoms, excluding 4-methyl-1-pentene (≧2.3% by weight) can form a non-porous skin layer. The highest α-olefin comonomer concentration having 2 to 20 carbon atoms, excluding 4-methyl-1-pentene, in a typical commercially available poly(methyl)pentene is about 6.7% by weight.

[0071] However, due to the high alpha-olefin comonomers of the materials used to make such layers, no porosity is induced in the PMP skin layer in the various implementations described herein. No solvent or phase inversion is used in the CELGARD® process to form the asymmetric hollow fibers. An exemplary method for producing a microporous asymmetric hollow fiber includes providing a poly(methyl)pentene (PMP) resin and a substrate resin, co-extruding the PMP resin and the substrate resin to form an asymmetric hollow fiber precursor, and stretching the asymmetric hollow fiber precursor to form an asymmetric hollow fiber having a PMP skin on the substrate.

[0072] [Optional nucleating agent] In certain exemplary embodiments, the porous substrate resin advantageously further comprises a nucleating agent in an amount effective to achieve nucleation. Suitable nucleating agents are known to those skilled in the art and include α-nucleating agents and β-nucleating agents.

[0073] The α-nucleating agent can be either a melt nucleating agent or an insoluble nucleating agent. A melt nucleating agent is a nucleating agent that melts during blending of the melt blend, but recrystallizes before the polymer separates from the mixture and crystallizes. Exemplary melt nucleating agents include, but are not limited to, arylalkanoic acid compounds, benzoic acid compounds, dicarboxylic acid compounds, and sorbitol acetal compounds.

[0074] Exemplary melt nucleating agents include, but are not limited to, dibenzylidine sorbitol, adipic acid, benzoic acid and sorbitol acetal compounds.Exemplary commercially available melt nucleating agents include, but are not limited to, MILLAD® 3988 and MILLAD® NX8000 available from Milliken Chemical (Spartanburg, SC), or NA-806A available from Amfine Chemical Corporation (Hasbrouck Heights, NJ).

[0075] An insoluble α-nucleating agent is a nucleating agent that does not melt during blending of the melt blend. In general, a material can be useful as an insoluble nucleating agent if it can be uniformly dispersed in the melt blend as discrete particles that can act as heterogeneous nucleation sites for the polymer components.

[0076] Exemplary insoluble nucleating agents include, but are not limited to, inorganic particulate materials and pigments. Exemplary inorganic particulate materials include, but are not limited to, bicyclo[2.2.1]heptane-2,3-dicarboxylic acid, disodium salt (available under the trade name HYPERFORM® HPN-20E from Milliken & Company, Spartanburg, SC), TiO2, talc, fine metal particles, or fine particles of polymeric materials such as polytetrafluoroethylene.

[0077] Exemplary pigments include, but are not limited to, copper phthalocyanine blue or green pigments, as well as D&C Red 6 (disodium salt). The particular nucleating agent used can be selected based on one or more criteria, such as the polyolefin (co)polymer used in the porous substrate, the desired pore size in a particular zone of the porous membrane, etc.

[0078] Alpha-nucleating agents only aid in the formation of alpha crystals (monoclinic crystal structure). There are also useful beta-nucleating agents that are effective in producing beta crystals (hexagonal unit cell crystal structure). Exemplary beta-nucleating agents include, but are not limited to, quinacridone dyes, aluminum salts of 6-quinazolinesulfonic acid, disodium salts o-phthalic acid, isophthalic acid and terephthalic acid, and N,N'-dicyclohexyl-2,6-naphthalenedicarboximide compounds. Exemplary commercially available beta-nucleating agents include, but are not limited to, MPM 2000, available from Mayzo, Inc. (Suwanee, GA).

[0079] Suitable nucleating agents for polyethylene (PE) porous substrate resins include, but are not limited to, inorganic nano-sized (i.e., having a particle size or diameter of less than 1 μm) fillers such as calcium carbonate, titanium dioxide, barium sulfate, silicon dioxide, graphite, carbon nanotubes, montmorillonite clay, talc, halloysite, or organic fillers such as ultra-high molecular weight PE, polymer fibers, anthracene, potassium hydrogen phthalate, benzoic acid type compounds, sodium benzoate type compounds, and monoglycerolate. Other suitable melt nucleating agents are listed in Polymer Engineering & Science, Vol. 5, (2016), page 541.

[0080] In some exemplary embodiments, a molten nucleating agent can be used alone. In other exemplary embodiments, an insoluble nucleating agent can be used alone. In some particular embodiments, a molten nucleating agent can be advantageously used in combination with an insoluble nucleating agent.

[0081] The nucleating agent is used in the melt blend in an amount sufficient to initiate crystallization of the polymer at the nucleation sites during fiber formation. The amount of nucleating agent required will depend at least in part on one or more of the particular (co)polymer used, the desired porosity and pore size, the particular nucleating agent used, and the like. In some exemplary embodiments, the melt blend can advantageously include 5% or less by weight of nucleating agent based on the total weight of the melt blend. In other exemplary embodiments, the melt blend can include between about 100 parts per million (ppm) and less than 5% by weight of nucleating agent based on the total weight of the melt blend. In further exemplary embodiments, the melt blend can include between 2% or less by weight of nucleating agent based on the total weight of the melt blend. In other exemplary embodiments, the melt blend can include between about 200 ppm and less than 2% by weight of nucleating agent based on the total weight of the melt blend.

[0082] [Method of manufacturing asymmetric hollow fiber member] In a further embodiment, the present disclosure describes a method of making an asymmetric hollow fiber membrane including providing a substrate resin and a skin layer resin, co-extruding the substrate resin and the skin layer resin to form an asymmetric hollow fiber membrane precursor, and stretching the asymmetric hollow fiber membrane precursor to form an asymmetric hollow fiber membrane having a skin layer made from the skin layer resin overlying a porous substrate made from the substrate resin and having a multiplicity of pores.

[0083] The base resin contains a semi-crystalline thermoplastic polymer (A) having a content of structural units (i) derived from 4-methyl-1-pentene of more than 99.4 mol % and not more than 100 mol %, and a content of structural units (ii) derived from at least one selected from α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) of 0 mol % or more and less than 0.6 mol % (the sum of the content of structural units (i) and the content of structural units (ii) is taken as 100 mol %). The skin layer resin contains a semi-crystalline thermoplastic copolymer (B) having a content of structural units (iii) derived from 4-methyl-1-pentene of 0.5% by mass or more and 98% by mass or less, and a content of structural units (iv) derived from at least one selected from α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) of 2% by mass or more and 99.5% by mass or less (the sum of the content of the structural units (iii) and the content of the structural units (iv) is 100% by mass).

[0084] Optionally, the α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene is selected from the group consisting of ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, isobutylene, vinylcyclohexane, 3-ethyl-1-pentene, 1,3-methyl-1-pentene, cyclobutene, cyclopentane, 2-norbornene, 3-methyl-2-norbornene, 5-methyl-2-norbornene, tetracyclododecene, methyltetracyclododecene, dimethyltetracyclododecene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-eicosene, or combinations thereof.

[0085] In some exemplary embodiments, the skin layer resin does not include a pore-forming material. In some such embodiments, step (1) of co-extruding the substrate resin and the skin layer resin to form an asymmetric hollow fiber membrane precursor includes step (3) of co-extruding the substrate resin and the skin layer resin through an annular co-extrusion die to form an asymmetric hollow fiber membrane precursor.

[0086] In certain exemplary embodiments, the method further comprises a step (4) of annealing the asymmetric hollow fiber precursor. Preferably, the step (4) of annealing the asymmetric hollow fiber precursor is performed before stretching the asymmetric hollow fiber precursor.

[0087] The microporous membranes described herein can be produced from a variety of production methods, depending on the desired asymmetric hollow fiber structure and the desired asymmetric hollow fiber composition. The microporous membranes can be made according to a variety of manufacturing techniques, such as the wet process, the dry stretch process (also known as the CELGARD process), and the particle stretch process.

[0088] Generally, in wet processes (also known as phase inversion, extraction, or TIPS processes), a polymeric feedstock is mixed with oil, processing oil, solvent, and / or other materials, the mixture is extruded, and pores are then formed when such oil, processing oil, solvent, and / or other materials are removed. These films may be stretched before or after removal of the oil, solvent, and / or other materials.

[0089] Generally, the microporous membranes are preferably formed via the CELGARD® process, also referred to as the "extrusion, annealing, stretch" or "dry stretch" process, whereby a semi-crystalline polymer is extruded to provide an asymmetric hollow fiber precursor and porosity is induced in the microporous substrate by stretching the extruded precursor.

[0090] Generally, in the particle stretching process, the polymer raw material is mixed with particles, the mixture is extruded, and pores are formed during stretching when the interface between the polymer and the particulates fractures due to the stretching force. The dry process differs from the wet process and the particle stretching process by producing porous asymmetric hollow fibers, typically without the addition of processing oils, oils, solvents, plasticizers, etc., or particulate materials. In general, the dry stretching process refers to a process in which pore formation results from stretching a non-porous precursor.

[0091] Although the membranes made by the dry stretching process have met with great commercial success, there is a need to improve their physical attributes so that they can be used in a wider range of applications.Thus, asymmetric hollow fibers are described that include a poly(methyl)pentene (PMP) skin disposed on a porous substrate to provide functionality that may be suitable for, for example, battery separators (useful in consumer electronics applications and electric or hybrid electric vehicle applications), blood oxygenation applications, blood filtration applications, various applications where liquids need to be degassed, and inkjet printing applications for degassing or degassing inks, and may also be well suited for use in hollow fiber asymmetric hollow fiber contactors or modules.

[0092] The method may also advantageously include a step (4) of annealing the asymmetric hollow fiber precursor prior to the stretching step. In an exemplary implementation, the annealing step (4) may include heating the asymmetric hollow fiber precursor at a temperature of about 150° C. for about 10 minutes.

[0093] Step (1) of co-extruding the PMP resin and the substrate resin to form an asymmetric hollow fiber precursor can include step (2) of extruding the PMP resin and the substrate resin through a co-extrusion die to form a PMP skin layer on the substrate layer. The co-extrusion die can be configured based on the desired thickness of the PMP skin layer and the substrate layer, and in an exemplary implementation, the substrate layer is thicker than the PMP skin layer.

[0094] Another exemplary method for making an asymmetric hollow fiber having a PMP skin and a porous polymer substrate as described herein can include steps (1) of providing a skin layer resin and a substrate resin, coextruding the skin layer resin and the substrate resin to form an asymmetric hollow fiber precursor, and (2) of stretching the asymmetric hollow fiber precursor to form an asymmetric microporous asymmetric hollow fiber having a skin layer on the porous substrate. The method can also include step (4) of annealing the asymmetric hollow fiber precursor prior to the stretching step.

[0095] Additional exemplary methods for producing asymmetric hollow fibers having the above PMP skin and porous polymer substrate include the steps of: providing a poly(methyl)pentene (PMP) resin and a substrate resin; co-extruding the PMP resin and the substrate resin to form an asymmetric hollow fiber precursor of a hollow fiber; and stretching the asymmetric hollow fiber precursor of a hollow fiber to form an asymmetric hollow fiber of a hollow fiber comprising a PMP skin on the substrate. The substrate resin may include one or more of PMP having a crystallinity different from that of the PMP skin, polyethylene (PE), polypropylene (PP), or a combination thereof. The method may also include the step of annealing the asymmetric hollow fiber precursor of a hollow fiber prior to the stretching step.

[0096] The stretching can be advantageously carried out using single-stage or multi-stage cold stretching, optionally followed by single-stage or multi-stage hot stretching. Preferably, the cold stretching temperature is selected to be between 20 and 90° C., more preferably between 30 and 70° C. Preferably, the hot stretching temperature is selected to be between 100 and 200° C., more preferably between 120 and 170° C.

[0097] The hollow fibers are advantageously stretched by uniaxial or biaxial elongation of at least 5% and up to 500%, more preferably at least 10% and up to 300%, to form an open porous structure.

[0098] The drawn hollow fibers can be advantageously exposed to a step of heat-setting to reduce stresses within the fiber. The heat-setting temperature is typically selected to be at least 5° C., at least 10° C., or even at least 15° C. higher than the hot drawing temperature. The heat-setting duration is typically selected to be at least 30 seconds, at least 1 minute.

[0099] Alternatively, the hollow fibers after drawing may be advantageously exposed to a relaxation step by allowing the fiber length to shrink to a certain extent, advantageously at least 2%, or even at least 5%. Heat setting and relaxation can be used alone or in combination.

[0100] [Hollow fiber membrane contactor] Referring again to the figures, Figure 1 shows an exemplary hollow fiber membrane contactor component 100 in which a plurality of asymmetric hollow fiber membranes 102 are arranged substantially parallel in an array pattern, in this case fastened together by braiding or tying the individual hollow fiber membranes 102 using strings, threads, yarns, or the like 104. Thus, in a further exemplary embodiment, the present disclosure describes a separation article including a multiplicity of asymmetric hollow fiber membranes according to any of the foregoing embodiments.

[0101] In some exemplary embodiments, multiple asymmetric hollow fiber membranes are arranged in an array, and in certain such embodiments, the array is pleated, folded, or wound into a cylinder or cassette.

[0102] In some exemplary embodiments, the separation article is selectively permeable to CO2 over N2 or CH4. The separation article preferably has a CO2 / N2 selectivity of 8 or greater, more preferably 9 or greater, and even more preferably 10 or greater. In other exemplary embodiments, the filtration article is selectively permeable to O2 over N2.

[0103] A hollow fiber membrane contactor typically includes a cylindrical bundle or mat of asymmetric hollow fibers and a rigid cylindrical shell or housing that encloses the fiber bundle. The shell can include multiple ports, for example, four fluid ports, an inlet for introducing a first fluid, an outlet for discharging the first fluid, an inlet for introducing a second fluid, and an outlet for discharging the second fluid. The hollow fibers can be embedded at both ends within the housing to form a polymeric tubesheet with fiber holes at each end opening into common first and second end cap portions of the shell.

[0104] The number of windings or layers of the hollow fiber array or fabric determines the depth of the panel. The end result is a hollow fiber array with height X, width Y, and depth Z. The hollow fiber array may be embedded directly into a square or rectangular frame in a shape similar to an HVAC air filter. In at least one embodiment, the gas to be treated passes through the contactor array on the shell side (outside the hollow fibers) in a cross-flow pattern with liquid (hot, cold, humidified, or absorbing liquid) passing through the cavity side (inside the hollow fibers) of the contactor array.

[0105] In at least certain embodiments, the present disclosure is directed to a method of producing or manufacturing an asymmetric hollow fiber membrane contactor. In at least one embodiment, a hollow fiber panel contactor is produced by a method that includes winding a hollow fiber membrane array around a paddle to form a square or rectangular fiber bundle. The number of windings or layers determines the depth or thickness of the panel. The end result is a fiber array having a height X, width Y, and depth Z. The wound array is then removed from the paddle and directly embedded into a square or rectangular frame similar in size and shape to a heating, ventilation, and air conditioning (HVAC) air filter.

[0106] If necessary, the ends of the hollow fibers are opened and a lumen-side fluid headspace is formed or added at each end. Such panel contactors are adapted to have air passing through the lumen-side (inside the hollow fibers) of the contactor array, or through the array on the shell-side (outside the hollow fibers) in a cross-flow pattern with a liquid (hot, cold, humidified, and / or absorbent liquid) to which a vacuum has been applied.

[0107] In at least one other embodiment, the panel contactor is produced by a method that includes pleating or folding (e.g., z-folding, accordion folding, or pleating, and then optionally rolling) a hollow fiber membrane array to form a fiber bundle in a square or rectangular format. The number of folds or layers can determine the depth of the panel. The end result is a fiber array having height X, width Y, and depth Z. The folded or pleated hollow fiber array may then be directly embedded into a square or rectangular frame in a shape similar to an HVAC air filter.

[0108] If necessary, the ends of the hollow fibers are opened and a lumen-side fluid headspace is formed or added at each end. Such panel contactors are adapted to have air passing through the lumen-side (inside the hollow fibers) of the contactor array, or through the array on the shell-side (outside the hollow fibers) in a cross-flow pattern with a liquid (hot, cold, humidified, and / or absorbent liquid) to which a vacuum has been applied.

[0109] In at least certain embodiments, the present disclosure is directed to a method or application of a flat panel hollow fiber array contactor. In at least one embodiment, the panel contactor is used by a method that includes passing air to be treated through the contactor array on the shell side (outside the hollow fibers) in a cross-flow pattern while simultaneously passing a liquid (hot, cold, humidified, and / or absorbent liquid) through the cavity side (inside the hollow fibers) of the contactor array. Thus, the contactor is a cavity side liquid contactor.

[0110] In at least one other embodiment, the panel contactor is used by or in a method that includes passing a liquid to be treated through the contactor array on the shell side (outside the hollow fibers) in a cross-flow pattern at the same time that a second liquid or gas passes through the lumen side (inside the hollow fibers) of the contactor array. Thus, the contactor is a shell-side liquid contactor.

[0111] Other uses of the disclosed panel contactors include CO2 scrubbing, greenhouse gas scrubbing, SO x Scrubs, no x Examples include scrubbing, HCl scrubbing, ammonia scrubbing, gas humidification, gas dehumidification, absorption of moisture and latent heat for energy recovery in HVAC systems, air emission control of off-flavors, e.g., in cattle or hog farms, and / or gas temperature control by varying humidity levels (such as in evaporative cooling or swamp coolers).

[0112] Thus, in accordance with at least selected embodiments of the present disclosure, the new or improved hollow fiber membrane contactors of the present invention address the shortcomings of conventional contactors, are effective for several applications, are specifically adapted for particular conditions, are readily familiar and acceptable to customers, do not use metal or other corrosive materials, do not use PVC, are modular, are replaceable, have standard air filter sizes, accommodate high air flow velocities, have low shell-side pressure drop, are commercially producible, and the like.

[0113] In at least one embodiment, a self-contained hollow fiber membrane contactor, filter or cartridge may include at least a first hollow fiber array including a plurality of at least a first hollow fiber membranes, each having a first end and a second end that are both open, at least one rectangular frame, shell, casing, or housing, and potting at each end. The first and second membrane ends are open, for example, to allow liquid to pass therethrough. It may be preferred that the hollow fibers are polyolefin, the frame is ABS, the potting is made of epoxy, and the ends of the potting are cut to form the first and second hollow fiber ends that are open after potting.

[0114] According to at least selected embodiments, a flat panel contactor combination or system includes two or more hollow fiber membrane panel contactors connected in series or parallel. According to at least certain potentially preferred embodiments, a flat panel contactor combination or system includes two or more hollow fiber membrane panel contactors connected in series with the frames of adjacent contactors abutting and aligned with one another (optional gaskets can be placed between the abutting frames and / or between the end frames and the ductwork to provide an airtight seal therebetween).

[0115] According to at least selected and possibly more preferred embodiments, the present panel membrane contactor (or membrane cartridge) preferably employs thousands of asymmetric microporous hollow fibers woven to include an arrangement that is wound, pleated, folded, and / or a combination thereof, for example, into a paddle or similar configuration. During preferred operation, air to be treated flows into the shell side (outside) of the hollow fibers, while liquid desiccant flows through or into the luminal or luminal side (inside) of the hollow fibers. Due to its hydrophobic nature, the membrane acts as an inert support, allowing direct contact between the gas and liquid phases without dispersion.

[0116] In accordance with certain embodiments of the present invention, novel contactors, contactor systems, methods, and / or the like are provided for treating one fluid with another fluid.

[0117] Typical applications include oxygen removal from boiler water, beverage carbonation, nitrogenation, and ink degassing. Systems used for gas generation / degassing are also known as membrane contactors. A gas-liquid interface is formed on the surface of a microporous membrane due to the hydrophobicity and small pore size of the fibers. The efficiency of hollow fiber membrane contactors is determined primarily by the membrane gas transfer rate, which depends on the fiber permeability and available fiber surface area within the module.

[0118] A typical hollow fiber membrane contactor consists of hundreds to thousands of asymmetric hollow fibers with a porosity of at least 40%. The smaller fiber diameter allows for higher fiber packing density, which can provide a higher total membrane surface area compared to flat sheet membranes.

[0119] [How to use hollow fiber membrane contactor] The present disclosure also describes a method of using any of the aforementioned separation articles, where the separation articles are used to separate a gas phase from a liquid phase. Thus, in a further exemplary embodiment, the present disclosure is directed to a method of using an asymmetric hollow fiber membrane contactor. Such an asymmetric hollow fiber membrane contactor and / or use can address one or more of the above-mentioned needs or shortcomings of conventional hollow fiber membranes.

[0120] In certain embodiments, the gas phase comprises N2, O2, CO2, CH4, or combinations thereof. In some such embodiments, the liquid phase comprises liquid water. In certain currently preferred embodiments, the liquid phase is an aqueous printing ink, or an aqueous brine (e.g., an aqueous well injection brine used in oil recovery).

[0121] In accordance with at least another embodiment of the present invention, a contactor system includes a liquid source, an air or gas source, at least one flat panel contactor including a plurality of asymmetric hollow fibers, and a rectangular frame, shell, housing, or vessel. The liquid source is preferably in fluid communication with the sheath of the hollow fibers. Air or gas is preferably passed over or across the fibers through the contactor.

[0122] Asymmetric hollow fiber membrane contactors may be used for many purposes, including but not limited to, removing entrained gas from liquids, degassing liquids, filtering liquids, and adding gas to liquids. More specifically, asymmetric hollow fiber membrane contactors may be advantageously used in removing entrained gas from inks used in printing.

[0123] In the gassing / degassing process, a continuous liquid / gas interface is created on the surface of the microporous fibers. In aqueous solutions, the liquid does not destroy the fibers due to the hydrophobicity and small pore size (50-100 nm) of polypropylene. The surface porosity allows for high-speed gas transport cross-fiber surface. However, typical hollow fiber membrane contactors can only process aqueous solutions.

[0124] In organic solvents or aqueous mixtures of water with high proportions (e.g., greater than 50% by weight, at least 60%, 70%, 80% or even 90% by weight) of organic solvent, wetting of the polyolefin pore walls is inevitable due to the low surface energy of the organic solvent and the polyolefin. Under such process conditions, hollow fiber membrane contactors may fail due to liquid collapse.

[0125] One approach to degassing organic solvents is the use of asymmetric polymethylpentene fibers that have an inherent thin non-porous skin layer with a porous substrate layer. The thin non-porous skin layer prevents liquid collapse while maintaining substantial gas permeability.

[0126] Asymmetric hollow fiber membrane contactors can also provide a means to achieve gas / gas, gas / liquid, and liquid / liquid (which may include liquid / dissolved solids) separation, transfer, or addition. Membrane contactors are typically used to contact two immiscible fluid phases, e.g., a first liquid and a second liquid, or a gas and a liquid, with each other to separate and / or transfer one or more components from one fluid to the other.

[0127] The operation of the present disclosure will be further described in connection with the following detailed examples. These examples are provided to further illustrate various specific preferred embodiments and techniques. However, it should be understood that many variations and modifications can be made while remaining within the scope of the present disclosure. EXAMPLES

[0128] These examples are merely illustrative and are not intended to unduly limit the scope of the appended claims. Although the numerical ranges and parameters setting forth the broad scope of the present disclosure are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. However, any numerical value inherently contains certain errors necessarily resulting from the standard deviation found in each testing measurement. At the very least, each numerical parameter should be construed by applying ordinary rounding techniques in light of the number of reported significant digits, but this is not intended to limit the application of the doctrine of equivalents to the scope of the claims.

[0129] <Test Method> The following test methods were used in evaluating some of the embodiments of the present disclosure.

[0130] [Gas permeability test] The gas permeability test is used as an integrity test for the non-porous skin layers as well as a performance test for the hollow fiber membranes.

[0131] Loop modules were prepared by sealing the hollow fibers together in ¼″ OD nylon tubing with Loctite® EA608 epoxy adhesive. After at least partial curing, the fiber cavities were exposed by cutting the sealing tube with a razor blade. Each loop module contained 10 fibers with an effective length of 4″ (approximately 10.2 cm).

[0132] Gas permeability testing was performed using a custom designed test stand. The stand was equipped with cylinders of pure gas (CO2 and N2), a pressure gauge, and an in-line gas flow meter. The principle of the test is to supply pure gas to the fiber lumen and measure the rate at which the gas escapes through the fiber wall to the surrounding environment. Both gas pressure and gas flow are monitored by the data acquisition software, and data is acquired when both pressure and gas flow are stabilized. Gas pressure in the fiber lumen was typically set to about 30 psi. Each fiber loop module was tested with CO2 and N2, respectively.

[0133] The gas permeability (GPU) of each membrane was calculated as follows:

number

number

[0134] Fiber gas selectivity has been used as an indicator of skin integrity. Selectivities for PMPs are typically in the range of 11-13, according to literature reports (Polymer, 1989, 30, p. 1357). Any fiber with a gas selectivity below 8 was considered to have a defective skin.

[0135] [Melting point (Tm), heat of fusion (ΔHm), crystallization temperature (Tc)] Using a Seiko Instruments DSC measuring device (DSC220C), about 5 mg of sample was packed in a measurement aluminum pan and heated to 280°C at 10°C / min. After holding at 280°C for 5 minutes, the temperature was lowered to 20°C at 10°C / min. After holding at 20°C for 5 minutes, the temperature was raised to 280°C at 10°C / min. The crystallization peak that appeared during the first temperature drop was taken as the crystallization temperature (Tc). The temperature at which the apex of the crystal melting peak observed during the second temperature rise appeared was taken as the melting point (Tm). The heat of fusion (ΔHm) was calculated from the integrated value of this crystal melting peak. When multiple peaks were detected during the measurement, the temperature at the peak detected on the highest temperature side and the integrated value of the peak were taken as the melting point, heat of fusion, and crystallization temperature, respectively.

[0136] [Melt flow rate (MFR)] The melt flow rate (MFR) was measured in accordance with ASTM D1238 at 260° C. under a load of 5 kg.

[0137] [Content of constituent units] The content of the constituent unit derived from 4-methyl-1-pentene and the content of the constituent unit derived from at least one selected from α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) in the polyolefin copolymer resin were measured by the following apparatus and conditions: 13 Calculated from C-NMR spectrum.

[0138] The Bruker Biospin AVANCEIIIcryo-500 nuclear magnetic resonance spectrometer was used. The solvent was a mixture of o-dichlorobenzene / benzene-d6 (4 / 1 v / v), the sample concentration was 55 mg / 0.6 mL, the measurement temperature was 120 °C, and the observed nuclei were 13 C (125 MHz), sequence was single pulse proton broadband decoupling, pulse width was 5.0 μs (45° pulse), repetition time was 5.5 s, and accumulation was 64 times. The chemical shift reference value was 128 ppm for benzene-d6. The content of α-olefin-derived structural units was calculated using the integral value of the main chain methine signal according to the following formula.

[0139] Content of α-olefin-derived structural units (%) = [P / (P+M)] × 100 Here, P denotes the total peak area of ​​the α-olefin main chain methine signals, and M denotes the total peak area of ​​the 4-methyl-1-pentene main chain methine signals.

[0140] [Vicat softening temperature] The injection molded products were subjected to a Vicat softening temperature test in accordance with ASTM D1525 using a test machine manufactured by Yasuda Seiki Co., Ltd., in silicone oil at a temperature rise rate of 50° C. per hour and with a test load of 10 N.

[0141] [Scanning Electron Microscope (SEM) Test] Scanning electron microscopy was used to determine the diameter of the hollow fiber membranes.

[0142] <Material Overview> All parts, percentages, ratios, etc. in the examples and elsewhere in the specification are by weight unless otherwise noted. Solvents and other reagents used are available from Sigma-Aldrich Chemical Company (Milwaukee, WI) unless otherwise noted. The following materials are used throughout the examples: N2, industrial grade nitrogen NI300, Airgas, Inc. (Radnor, PA); CO2, Instrument 4.0 Grade Carbon Dioxide CDI200, Airgas (Radnor, PA), 1 / 4" nylon tubing, NewAge Industries Company (Southampton, PA), Loctite EA 608 Hysol, Henkel Corporation (Rocky Hill, CT), Deuterated orthodichlorobenzene (ODCB), Sigma-Aldrich (St. Louis, MO); Chromium(III) acetylacetonate, (Cr(acac)4), Sigma-Aldrich (St. Louis, MO).

[0143] The compositions constituting the skin layer and the substrate layer were obtained as follows.

[0144] Preparation of catalyst (Production of Transition Metal Compound (A)) According to Synthesis Example 4 of WO 2014 / 050817, (8-octamethylfluoren-12′-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride (transition metal compound (A)) was synthesized.

[0145] (Preparation of solid catalyst component) At 30°C, 32mL of purified decane and 14.65mmol of solid polymethylaluminoxane (manufactured by Toso Finechem Co., Ltd.) were charged under nitrogen flow into a 100mL three-necked flask equipped with a stirrer that had been thoroughly substituted with nitrogen, to prepare a suspension. 50mg of the previously synthesized transition metal compound (A) (0.059mmol in terms of zirconium atom) was dissolved in 4.6mmol / L toluene, and 12.75mL of this solution was added to the suspension while stirring. After 1.5 hours, stirring was stopped, and the obtained catalyst component was washed three times with 50mL of decane by decantation, and suspended in decane to obtain 50mL of slurry (B). The Zr loading rate in this catalyst component was 100%.

[0146] (Preparation of Prepolymerized Catalyst Component) To the slurry liquid (B) prepared above, 2.0 mL of a decane solution of diisobutylaluminum hydride (2.0 mmol / mL in terms of aluminum atom) and 7.5 mL (5.0 g) of 4-methyl-1-pentene were added under a nitrogen stream. After 1.5 hours, stirring was stopped, and the obtained prepolymerized catalyst component was washed three times with 50 mL of decane by decantation. This prepolymerized catalyst component was suspended in decane to obtain 50 mL of decane slurry (C). The concentration of the prepolymerized catalyst component in the decane slurry (C) was 20 g / L, 1.05 mmol-Zr / L, and the Zr recovery rate was 90%.

[0147] [Polymer (A1)] (Production of Polymer (A1)) At room temperature and under nitrogen flow, 425 mL of purified decane and 0.5 mL (1 mol) of a decane solution of diisobutylaluminum hydride (2.0 mmol / mL in terms of aluminum atoms) were charged into a SUS polymerization vessel equipped with a stirrer having an internal volume of 1 L. Next, 0.0005 mmol of the previously prepared prepolymerized catalyst component slurry solution (C) in terms of zirconium atoms was added, and 47 NmL of hydrogen was charged. Next, 250 mL of 4-methyl-1-pentene was continuously charged into the polymerization vessel at a constant rate over 2 hours. The start of this charging was regarded as the start of polymerization, and the temperature was raised to 45°C over 30 minutes from the start of polymerization, and then the temperature was maintained at 45°C for 4 hours. 47 NmL of hydrogen was charged one hour and two hours after the start of polymerization. After 4.5 hours had passed since the start of polymerization, the temperature was lowered to room temperature, the pressure was removed, and the polymerization liquid containing a white solid was immediately filtered to obtain a solid substance. This solid substance was dried under reduced pressure at 80° C. for 8 hours to obtain polymer (A1). The yield was 131 g. The analytical results of the obtained polymer (A1) are shown in Table 1.

[0148] (Preparation of pellets for evaluation) Polymerization was carried out multiple times as necessary to prepare a sufficient amount of polymer for pellet production. 0.1 parts by mass of tri(2,4-di-t-butylphenyl)phosphate as a secondary antioxidant and 0.1 parts by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were blended with 100 parts by mass of the polymer obtained above. Then, pellets for evaluation were obtained by granulating using a twin-screw extruder BT-30 (screw diameter 30 mmφ, L / D 46) manufactured by Plastics Engineering Research Institute Co., Ltd. under the conditions of a set temperature of 260°C, a resin extrusion rate of 60 g / min, and a rotation speed of 200 rpm. The obtained evaluation pellets were used to carry out MFR measurement and DSC measurement by the above-mentioned methods. The results are shown in Table 1.

[0149] (Preparation of injection molded body) Using the above evaluation pellets, the first injection was performed at 320 kg / cm using an injection molding machine M70B manufactured by Meiki Seisakusho Co., Ltd. under the conditions of a cylinder temperature of 300°C and a mold temperature of 65°C. 2 This is done over 5 seconds, followed by a second injection at 260kg / cm 2 The injection molding was performed for 3 seconds at 100° C. to obtain an IS dumbbell-shaped (ISO3167:93) injection molded article with a thickness of 4 mm and a parallel part of 80 mm. The Vicat softening temperature of the obtained injection molded article was measured by the method described above. The results are shown in Table 1.

[0150] [Polymer (A2), Copolymers (B1) to (B3)] (Production and Evaluation of Polymer (A2) and Copolymers (B1) to (B3)) According to the methods of Comparative Examples 7 and 9 of WO 2006 / 054613, the ratios of 4-methyl-1-pentene, 1-decene, 1-hexadecene, 1-octadecene, and hydrogen were changed to obtain polymer (A2) and copolymers (B1) to (B3). The analysis results are shown in Table 1. Furthermore, pellets for evaluation and injection molded articles were prepared using each of the obtained polymers in the same manner as in Example 1, and each was evaluated by the above-mentioned method. The results of the obtained polymer (A2) and copolymers (B1) to (B3) are shown in Table 1.

[0151] In addition, Table 1 provides the abbreviations, properties, and compositions of the polyolefin copolymer resins used in the following examples, where "PMP" refers to the polyolefin copolymer segment derived from 4-methyl-1-pentene monomer, Tm refers to the melting temperature obtained using differential scanning calorimetry (DSC), and ΔHm is the heat of fusion (dissolution) obtained using the above-mentioned differential scanning calorimetry (DSC) and nuclear magnetic resonance (NMR) tests.

[0152] [Table 1]

[0153] <Apparatus and Method> [Apparatus for manufacturing co-extruded hollow fiber membranes] The dual layer hollow fiber precursors were coextruded through a twin orifice annular ring die (available from Guill Tools, West Warwick, RI) with a central air hole using two Haake single screw extruders available from ThermoFisher Scientific (Grand Island, NY). The substrate resin was extruded through the central core of the die and the skin layer resin was extruded through the annular rings of the die.

[0154] After exiting the die, the molten hollow fiber precursor was solidified through a quench ring, and the hollow fiber precursor was collected by passing it over motor-driven godet rollers and winding it onto a tension-controlled spool.

[0155] [Manufacturing process of co-extruded hollow fiber membrane] 1. Hollow fiber membrane precursor extrusion molding The skin layer and porous substrate resins were fed into two single screw extruders, respectively. The substrate resin was extruded in a 3 / 4" (1.91 cm) extruder with 24 L / D, and the skin layer resin was extruded in a 1 / 2" (1.27 cm) extruder with a smaller output. The three-zone porous substrate resin extruder was controlled at temperatures of 215°C, 240°C, and 260°C from zone 1 to zone 3, while the three-zone skin layer resin extruder used a temperature range of 235-270°C for zones 1-3. The extrusion die temperatures were set at 260°C to 275°C.

[0156] The two melt resin streams were metered through a two orifice die. The two melt streams converge inside the die less than 5 mm away from the die face. To ensure uniformity of the walls and layers of the two-layer hollow fiber membrane, the orifices in the die were fine-tuned to maintain good concentricity. The extrusion rate of the skin layer resin was kept significantly lower than that of the porous substrate resin to reduce the thickness of the skin layer.

[0157] A low volume air flow was supplied to the central hole of the annular die to prevent the fibers from collapsing or blowing down. The molten fibers were solidified by passing through an air quench ring. The diameter of the hollow fiber was controlled by drawing with a motor-driven godet roll. The drawing speed was set at 100 meters per minute. The resulting hollow fiber membrane precursor was collected with a low tension spooler.

[0158] 2. Hollow fiber membrane annealing A 10" (25.4 cm) hollow fiber precursor bundle was prepared and each end was taped together using high temperature tape. The bundle was annealed in a convection oven set at a temperature of 145-160°C. The annealing time for each fiber precursor bundle was 10 minutes.

[0159] 3. Hollow fiber membrane stretching (cold / hot) and heat curing A bundle of 40-45 annealed fibers was clamped in the temperature-controlled environmental chamber of an Instron Mechanical Tester (Model #5567, Morwood, MA).

[0160] The fibers were cold drawn at 23°C to an elongation (draw) ratio of 15-20% using a draw speed of 10 in / min (25.4 cm / min) and then hot drawn at 150°C to an elongation (draw) ratio of 25% using a draw speed of 1 in / min (2.54 cm / min).

[0161] The fiber was held under tension during a temperature gradient from 23°C to 150°C. No relaxation of the fiber was observed after hot drawing. After the chamber temperature was cooled to below 40°C, the fiber was released from the Instron mechanical tester. The specific process conditions used in the examples and comparative examples are shown in Tables 2 and 3.

[0162] [Table 2]

[0163] [Table 3]

[0164] The following comparative examples and examples show an approach to selecting a suitable resin of PMP for the skin layer, which remains defect-free (non-porous structure) after extrusion, annealing, and stretching, while the substrate layer produces a porous structure and can function as a support with little gas transmission resistance.

[0165] [Example 1] Skin layer: copolymer (B1) / Base layer: polymer (A1) Copolymer (B1) was used for the skin layer, and polymer (A1) was used for the porous substrate layer. Copolymer (B1) is a low modulus PMP with a low melt flow index. Polymer (A1) is a high modulus PMP with a low melt flow index. The resulting coextruded asymmetric hollow fiber membrane was tested according to the gas permeability test and exhibited a CO2 / N2 selectivity of 13.0 and a CO2 gas permeation rate of 35.9 GPU, as summarized in Table 4.

[0166] [Example 2] Skin layer: copolymer (B2) / Base layer: polymer (A1) Copolymer (B2) was used for the skin layer, and polymer (A1) was used for the porous substrate layer. Copolymer (B2) is a low modulus PMP with a high melt flow index. Polymer (A1) is a high modulus PMP with a low melt flow index. The resulting coextruded asymmetric hollow fiber membrane was tested according to the gas permeability test and exhibited a CO2 / N2 selectivity of 13.0 and a CO2 gas permeation rate of 33.4 GPU, as summarized in Table 4.

[0167] [Example 3] Skin layer: copolymer (B3) / Base layer: polymer (A1) Copolymer (B3) was used for the skin layer, and polymer (A1) was used for the porous substrate layer. Copolymer (B3) is a medium modulus PMP with a low melt flow index. Polymer (A1) is a high modulus PMP with a low melt flow index. The resulting coextruded asymmetric hollow fiber membrane was tested according to the gas permeability test and exhibited a CO2 / N2 selectivity of 13.0 and a CO2 gas permeation rate of 48.1 GPU, as summarized in Table 4.

[0168] [Comparative Example 1] Skin layer: copolymer (B1) / Base layer: polymer (A2) Copolymer (B1) was used for the skin layer, and polymer (A2) was used for the porous substrate layer. Copolymer (B1) is a low modulus PMP with a low melt flow index. Polymer (A2) is a high modulus PMP with a low melt flow index. The resulting coextruded asymmetric hollow fiber membrane was tested according to the gas permeability test and exhibited a CO2 / N2 selectivity of 13.1 and a CO2 permeation rate of 23.7 GPU, as summarized in Table 4.

[0169] [Comparative Example 2] Skin layer: copolymer (B2) / Base layer: polymer (A2) Copolymer (B2) was used for the skin layer, and polymer (A2) was used for the porous substrate layer. Copolymer (B2) is a low modulus PMP with a high melt flow index. Polymer (A2) is a high modulus PMP with a low melt flow index. The resulting coextruded asymmetric hollow fiber membrane was tested according to the gas permeability test and exhibited a CO2 / N2 selectivity of 13.8 and a CO2 gas permeation rate of 21.2 GPU, as summarized in Table 4.

[0170] [Comparative Example 3] Skin layer: copolymer (B3) / Base layer: polymer (A2) Copolymer (B3) was used for the skin layer, and polymer (A2) was used for the porous substrate layer. Copolymer (B3) is a medium modulus PMP with a low melt flow index. Polymer (A2) is a high modulus PMP with a low melt flow index. The resulting coextruded asymmetric hollow fiber membrane was tested according to the gas permeability test and exhibited a CO2 / N2 selectivity of 13.1 and a CO2 permeability of 35.9 GPU, as summarized in Table 4.

[0171] [Table 4]

[0172] Throughout this specification, references to "one embodiment," "a particular embodiment," "one or more embodiments," or "an embodiment" mean that the particular feature, structure, material, or characteristic described in connection with that embodiment is included in at least one of the particular exemplary embodiments of the disclosure, regardless of whether the term "exemplary" is included before the term "embodiment." Thus, the appearances of phrases such as "in one or more embodiments," "in a particular embodiment," "in one embodiment," or "in an embodiment" in various places throughout this specification do not necessarily refer to the same particular exemplary embodiments of the disclosure. Furthermore, particular features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments.

[0173] Although some exemplary embodiments have been described in detail herein, it is understood that those skilled in the art can easily imagine modifications, variations, and equivalents of these embodiments after understanding the above description. Therefore, it should be understood that the present disclosure is not unduly limited to the exemplary embodiments described so far. In particular, as used herein, the recitation of numerical ranges by endpoints is intended to include all numbers subsumed within that range (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, and 5). In addition, all numbers used herein are intended to be modified by the term "about."

[0174] Furthermore, all publications and patents referenced in this specification are incorporated by reference in their entirety to the same extent as if each individual publication or patent was specifically and individually indicated to be incorporated by reference. Various exemplary embodiments have been described. These and other embodiments are within the scope of the following claims. [Explanation of symbols]

[0175] 100...Hollow fiber membrane contactor components 102...Asymmetric hollow fiber membrane 104···String 202...Asymmetric hollow fiber membrane 204...Porous base material 206 Skin layer 308...Pore 310...Surface of porous substrate

Claims

1. A porous substrate comprising a semi-crystalline thermoplastic polymer (A) having a plurality of pores, a content of 4-methyl-1-pentene-derived structural unit (i) of more than 99.4 mol% and not more than 100 mol%, and a content of at least one structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) of 0 mol% or more and less than 0.6 mol% (the sum of the content of the structural unit (i) and the content of the structural unit (ii) is 100 mol%); a skin layer comprising a semi-crystalline thermoplastic copolymer (B) having a content of 0.5% by mass or more and 98% by mass or less of structural units (iii) derived from 4-methyl-1-pentene and a content of 2% by mass or more and 99.5% by mass or less of structural units (iv) derived from at least one selected from α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) (the sum of the content of the structural units (iii) and the content of the structural units (iv) is 100% by mass); An asymmetric hollow fiber membrane comprising:

2. 2. The asymmetric hollow fiber membrane of claim 1, wherein the plurality of pores comprises a plurality of micropores, the plurality of micropores having a diameter of 0.01 to 1.0 μm.

3. The asymmetric hollow fiber membrane according to claim 1, wherein the porosity of the asymmetric hollow fiber membrane is 5 to 80%.

4. 2. The asymmetric hollow fiber membrane of claim 1, wherein the skin layer has a lower porosity than the porous substrate, the outer surface of the asymmetric hollow fiber membrane constitutes a sheath, and the porous substrate constitutes an inner lumen surface of the asymmetric hollow fiber membrane.

5. 5. The asymmetric hollow fiber membrane of claim 4, wherein the skin layer is non-porous.

6. 2. The asymmetric hollow fiber membrane according to claim 1, wherein the porous substrate further comprises 200 ppm to 5% by mass of a nucleating agent (wherein the porous substrate is taken as 100% by mass).

7. 2. The asymmetric hollow fiber membrane according to claim 1, wherein the skin layer has a thickness of 1.0 μm or more and less than 20 μm.

8. The asymmetric hollow fiber membrane according to claim 1, wherein the porous substrate has a thickness of 5 to 200 μm.

9. 2. The asymmetric hollow fiber membrane of claim 1, wherein the asymmetric hollow fiber membrane is a heterogeneous asymmetric hollow fiber membrane.

10. 2. The asymmetric hollow fiber membrane of claim 1, wherein the skin layer completely covers the porous substrate.

11. A separation article comprising a plurality of the asymmetric hollow fiber membranes of claim 1.

12. 12. The separation article of claim 11, wherein the plurality of asymmetric hollow fiber membranes are arranged in an array and the array is pleated, folded, or rolled into a cylinder or cassette.

13. N 2 or CH 4 More than CO 2 The separation article of claim 11 , wherein the article is selectively permeable to

14. CO 2 / N 2 or CO 2 / CH 4 14. The separation article of claim 13, wherein the selectivity is 8 or greater.

15. N 2 More than O 2 The separation article of claim 11 , wherein the article is selectively permeable to

16. A method for producing an asymmetric hollow fiber membrane comprising a porous substrate and a skin layer, comprising the steps of: The base resin constituting the porous base material contains a semi-crystalline thermoplastic polymer (A) having a content of 4-methyl-1-pentene-derived structural unit (i) of more than 99.4 mol% and 100 mol% or less, and a content of at least one structural unit (ii) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) of 0 mol% or more and less than 0.6 mol% (the sum of the content of the structural unit (i) and the content of the structural unit (ii) is 100 mol%); the skin layer resin constituting the skin layer contains a semi-crystalline thermoplastic copolymer (B) having a content of 4-methyl-1-pentene-derived structural unit (iii) of 0.5% by mass or more and 98% by mass or less and a content of at least one structural unit (iv) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) of 2% by mass or more and 99.5% by mass or less (the sum of the content of the structural unit (iii) and the content of the structural unit (iv) is 100% by mass); (1) co-extruding the substrate resin and the skin layer resin to form an asymmetric hollow fiber membrane precursor; (2) stretching the asymmetric hollow fiber membrane precursor to form an asymmetric hollow fiber membrane having a skin layer composed of the skin layer resin on a porous substrate composed of the base resin and including a plurality of pores; A method for producing an asymmetric hollow fiber membrane comprising the steps of:

17. 17. The method of claim 16, wherein the skin layer resin does not contain a pore-forming material.

18. 18. The method for producing an asymmetric hollow fiber membrane according to claim 17, wherein the step (1) comprises a step (3) of co-extruding the base resin and the skin layer resin through an annular co-extrusion die to form the asymmetric hollow fiber precursor.

19. The method for producing an asymmetric hollow fiber membrane according to claim 16, further comprising a step (4) of annealing the asymmetric hollow fiber precursor.

20. The method for producing an asymmetric hollow fiber membrane according to claim 19, wherein the step (4) is carried out before stretching the asymmetric hollow fiber precursor.

Citation Information

Patent Citations

  • Method of preparing gas selective membrane using epoxy-functional siloxanes

    WO2012138755A1

  • Adeno-associated virus purification methods

    WO2018128688A1